1128 Ultrasound scan of sacral dimples and other associated cutaneous stigmata in infants: an audit of local practice. (17th August 2022) - Kini, Prashant; Heaton, Paul; Giri, Barbie; Paul, SIba
Abstract : Aims: The Royal College of Radiologists (RCR) guidelines published in 2007 entitled 'Making the best use of clinical radiology services: referral guidelines' 6th edn. Advises the use of ultrasound scanning to investigate pathology associated with a sacral dimple (or other associated cutaneous stigmata) in neonates. An audit conducted in 2016 showed that in our centre over a 3½-year period only 1 case of sacral lipoma was identified from 21 babies who were scanned. Our centre serves a population with approximately 1600 deliveries each year. A re-audit was undertaken in 2021 to determine whether recommendations from the previous audit had been implemented, and to identify any potential improvements in our practice. Methods: Patients were identified from the radiology database between June 2016 and April 2021. Clinical notes and electronic databases were analysed, and the following data was recorded: whether referral criteria had been followed, lesions identified, source of referral, and timing of ultrasound scans. Where possible, information on appropriateness of referral (determined after the audit in 2016) was collected and compared to our five referral criteria: 1. Sacral dimple visible without a base 2. Median or paramedical masses, haemangioma or skin tags 3. Tuft of hair 4. Lower limb weakness 5. High lying sacral dimple (lies >2.5cm above the anus) Results: Over the 5-year period, 49 infants had spinal ultrasound scans; 25/49 were females (51%); 38/49 (78%) infants were scanned at <3 months of age and 11 were aged 3-6 months. Ten babies (20% of cases) were referred by general practitioners. Initial scans revealed abnormal findings in 5/49 cases; on further review/imaging each of the 5 cases was determined have findings of no major clinical significance. 26/49 (53%) cases matched our referral criteria for high-risk groups. Conclusion: The re-audit conducted 5 years following the original study identified that a significant proportion of cases (47%) did not meet the recommended referral criteria. Over a 8½-year period in out centre, a total of 70 infants underwent ultrasound scans. Only 1 case, who had a sacral pit and an abnormal tuft of hair, was considered to need intervention. Teaching sessions to improve compliance with referral recommendations are being organised locally for paediatric doctors and general practitioners. There is need for robust guidance from the RCR to improve clinical practice.